Development of logistics management in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
This article discusses the role of logistics management in the Republic of Kazakhstan and impact to logistics activities, provides general and specific principles, composition and structure of the logistics system, the functions and methodological tools for management of the resource potential of the system, it is proposed organizational and functional structure consisting of functional and providing subsystems. Provided that in the current context of global logistics plays a key role in the industrial development of the state and discusses the role of logistics management as the most important factor to stimulate industrial development in the Republic of Kazakhstan. Considering the problems such as underdeveloped transport infrastructure and storage facilities, poor quality of services, low professionalism of the domestic logistics operators on the one hand, and greater opportunities associated with the construction of the road Western Europe – Western China on the other, and has offered optimal solutions.